Real-world patient outcomes with Blinatumomab and Inotuzumab in adult relapsed/refractory B-cell acute lymphoblastic leukemia: a retrospective analysis from two Romanian oncology centers - Antohe, Ion; Titieanu, Amalia; Cianga, Vlad Andrei; Minciună, Cosmin; Dănăilă, Cătălin; Tănase, Alina Daniela; Ivanov, Iuliu; Dragoş, Loredana; Zlei, Mihaela; Mențel, Mihaela; Tomuleasa, Ciprian; Bancos, Anamaria; et al. (Frontiers in Pharmacology, 2025)
IntroductionThe management of adult relapsed/refractory B-cell acute lymphoblastic leukemia (R/R B-ALL) remains a significant challenge, with patients presenting particularly poor historical outcomes. Novel immunotherapies, such as Blinatumomab and Inotuzumab, have revived the therapeutic landscape of R/R B-ALL, but their optimal sequencing, toxicity management, and post-transplant integration remain unclear, particularly in real-world, resource-limited settings.MethodsWe conducted a retrospective analysis of 33 adult patients with R/R B-ALL treated between 2019 and 2023 at two major oncology centers in Romania.ResultsBlinatumomab and Inotuzumab achieved complete remission rates of 47.6% and 90%, respectively, with measurable residual disease negativity in over 60% of responders. Inotuzumab was more effective in early relapses and cases with high disease burden, while Blinatumomab showed benefit in later relapses and post-transplant settings. Eleven patients were successfully bridged to allogeneic stem cell transplant, and four were treated for post-transplant relapse, demonstrating the feasibility of immunotherapy in both contexts. Sequential monoclonal antibody use yielded poor survival unless used as a bridge to curative therapy.ConclusionOur findings emphasize the need for individualized treatment selection, rational immunotherapy sequencing, and the development of predictive biomarkers to optimize outcomes and minimize toxicity. Further studies are needed to refine therapeutic algorithms and define such prognostic biomarkers, particularly in underfunded healthcare systems.